2013
DOI: 10.5194/acp-13-1957-2013
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layer nucleation as a source of new CCN in savannah environment

Abstract: The South African savannah region is a complex environment of air pollution and natural emissions influenced by a strong seasonal cycle in biomass burning and strong precipitation. However, the scarcity of long-term observations means that the knowledge of controlling aerosol processes in this environment is limited. Here we use a recent dataset of 18 months of aerosol size distribution observations trying to understand the annual cycle of cloud condensation nuclei (CCN). <br><br> Our observations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 74 publications
2
36
1
Order By: Relevance
“…The observed values of GR on 29, 30 and 31 August were 3.3, 1.8 and 3.6 nm h −1 , respectively, which are lower than the annually averaged (±SD) GR of 5.2 ± 3.4 nm h −1 reported by Pikridas et al (2012) at the same site for the 10-25 nm size range. By following the approach of Laakso et al (2013), we could follow the growth of newly formed particles up to about 50-60 nm in particle diameter until another NPF occurred or the particle growth was interrupted by an air mass or cloud cover change. These features are suggestive of the convolution of nucleation with condensational growth of both new and preexisting particles formed in the previous day (or even earlier) to produce CCN size range particles.…”
Section: Aerosol Growth and Ccn Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed values of GR on 29, 30 and 31 August were 3.3, 1.8 and 3.6 nm h −1 , respectively, which are lower than the annually averaged (±SD) GR of 5.2 ± 3.4 nm h −1 reported by Pikridas et al (2012) at the same site for the 10-25 nm size range. By following the approach of Laakso et al (2013), we could follow the growth of newly formed particles up to about 50-60 nm in particle diameter until another NPF occurred or the particle growth was interrupted by an air mass or cloud cover change. These features are suggestive of the convolution of nucleation with condensational growth of both new and preexisting particles formed in the previous day (or even earlier) to produce CCN size range particles.…”
Section: Aerosol Growth and Ccn Productionmentioning
confidence: 99%
“…When no CCN measurements are available, a commonly used proxy for the CCN number concentration is the total number concentration of particles larger than some threshold diameter, D, denoted as N D (Paasonen et al, 2013;Laakso et al, 2013). Just prior to the nucleation event period (28 August-2 September) and after it, our CCN counter was offline the DMA due to technical problems, so that it was recording the total CCN number concentration at 0.2 % supersaturation, CCN 0.2 .…”
Section: Atmosmentioning
confidence: 99%
“…Many other studies using global aerosol-climate models have demonstrated the importance of atmospheric NPF for regional and global aerosol number concentration and cloud condensation nuclei budgets (Merikanto et al, 2009;Pierce et al, 2007;Pierce and Adams, 2009;Wang and Penner, 2009;Yu and Luo, 2009;Trivitayanurak et al, 2008;Jung et al, 2010;Laakso et al, 2013;Scott et al, 2014), each study assessing which parametrization leads to the best agreement with observations in their model. Global models have a large grid size (usually 200-300 km when aerosols are included), hence the number concentration of newly formed particles and size distribution are prone to large uncertainties.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Beukes et al (2014), Laakso et al (2013) and Venter et al (2012) indicated that O 3 is currently the most problematic pollutant in South Africa. Tropospheric O 3 impacts air quality, food security (Zunckel et al, 2006) and regional climate change (Fry et al, 2013).…”
Section: O 3 Formation Potential Of Aromatic Hydrocarbonsmentioning
confidence: 99%